Assessment of vegetative Phenology with respect to leaf elongation pattern of Avicennia marina and Rhizophora mucronata in Hajambro creek, Indus delta, Pakistan - Farooqui, Zafar; Siddiqui, Pirzada Jamal (Journal of Tropical Life Science, 2014)
Leaves emergence and the rate of elongation have been studied in Hajambro creek in Indus deltaic region, Pakistan. Leaves emergence was found higher during the summer months (mostly pre-monsoon period), that was March April, May and June. Leaves of A. marina that were observed from March to July, till the leaves reached their maximum length (about 77 mm), showed a gradual increase in their length, reaching maximum in April. Leaves of Avicennia marina reached their maximum length (about 77 mm) in about 113 days. The leaves showed gradual increase in their length, reaching maximum in April (0.97mm d-1). The per-day increment in length was 0.54 mm d-1. As reaching their maximum length (77mm), the per-day increment in the length gradually slower down. The leaves of Rhizophora mucronata were observed from February to November. The leaves of Rhizophora mucronata showed elongation rate of 0.24 mm d-1 from the day of the first observation till the leaves reached their maximum length (120 mm). The maximum time required by the leaves to reach their maximum length (120 mm) was 236 days. The rates of elongation of leaves are also fast in summer. The rate of elongation of the leaves was found to be highly correlated with the temperature (p